Covid-19 vaccine, acceptance, and concern of safety from public perspective in the state of Odisha, India - Dibya Sundar Panda; Ranjan Kumar Giri; Anil Kumar Nagarajappa; Sakeenabi Basha (Taylor & Francis Group, 2021)
Introduction: No medication or therapies were found to be effective in controlling the covid-19 pandemic. The fast-track development of covid-19 vaccine brought some hope among health practitioners globally. The major challenge seems to be safety, efficacy, and acceptance of the vaccine. A cross-sectional survey was conducted among the community of the state of Odisha, India, to find out the concerns of safety and acceptance for the vaccine. Methods: A self-administered multiple-choice questionnaire containing 23 items with three sections was prepared in Google form and deployed following snow ball sampling method. The participants recruited were above 18 years of age residing in Odisha. The participation in the survey was completely voluntary. The survey was conducted during February 2021. Results and discussion: In total, 359 members participated in the survey. Majority of the respondent strongly agree/agree that covid-19 vaccine is safe for adults and children. Significant variation among all the groups was found regarding acquisition of higher immunity following infection rather by vaccination, effectiveness in infection prevention, safety in children, provision of mandatory vaccination by government, and public health protection following government guidelines. Conclusion: The major barrier to the covid-19 vaccination was found to be safety and awareness. But there is well acceptance to covid-19 vaccine among the community of Odisha, India, and further efforts to create awareness concerning safety and vaccination will be instrumental in the eradication of this infection.